Effect of angiotensin receptor blockers on blood pressure and renal function in patients with concomitant hypertension and chronic kidney disease: a systematic review and meta-analysis. (2nd November 2019) - Burnier, Michel; Lin, Shanyan; Ruilope, Luis; Bader, Giovanni; Durg, Sharanbasappa; Brunel, Patrick
Abstract: Objective: Angiotensin receptor blockers (ARB) are among the recommended first-line treatment options in patients with hypertension and chronic kidney disease (CKD). This meta-analysis evaluated the effect of ARB on blood pressure (BP) and renal function in patients with concomitant hypertension and CKD with or without diabetes. Methods: Literature search was performed in PubMed/MEDLINE, EMBASE and BIOSIS to identify parallel-group, randomized controlled trials (≥8 weeks) reporting the effects of ARB on office systolic/diastolic BP (SBP/DBP), estimated glomerular filtration rate (eGFR), serum creatinine (SCr), creatinine clearance (CrCl) or proteinuria in adults with hypertension and CKD. Mean difference (MD, generic inverse variance) with 95% confidence intervals (CIs) was used to report an outcome. Results: Among the 24 studies identified, 19 evaluated ARB as monotherapy, 4 evaluated ARB as combination therapy and one evaluated ARB both as monotherapy and combination therapy. Median (range) duration of the studies was 12 (1.84–54.0) months. ARB monotherapy significantly ( p < 0.01) reduced BP (treatment ≥1 year: SBP [MD: −14.84 mmHg; 95% CI: −17.82 to −11.85]/DBP [−10.27 mmHg; −12.26 to −8.27]) and proteinuria (≥1 year [−0.90 g/L; −1.22 to −0.59]). Results were consistent for combination therapy. In these studies, non-significant changes were observed for eGFR, CrCl and SCr. The impact of SBP changes on eGFR was not significant; however, studies were of a relatively short duration. Conclusion: ARB had a favorable impact on BP and renal parameters such as proteinuria with monotherapy as well as with combination therapy, highlighting their potential benefits in patients with hypertension and CKD. During the short follow-up of these studies, no significant change in eGFR was observed.